BROADCASTING AND VIEWS OF FEATURE FILMS ON RUSSIAN TELEVISION: TRENDS OF 2018–2019 / ТРАНСЛЯЦИИ И ПРОСМОТРЫ ХУДОЖЕСТВЕННЫХ ФИЛЬМОВ НА РОССИЙСКОМ ТЕЛЕВИДЕНИИ: ТЕНДЕНЦИИ 2018–2019 ГОДОВ - SHARIKOV ALEXANDER V. / ШАРИКОВ А.В, (Наука телевидения)
The article describes the results of an empirical study aimed at identifying the latest trends in broadcasting and viewing of feature films on leading Russian television channels in 2018–2019. On the basis of the Mediascope database, films broadcast on 29 leading Russian channels for the period from December 31, 2017 to March 10, 2019 were analyzed. 23548 items describing feature films were broadcast on 26 television channels, on average—14.7 a week, 2.1 a day per channel. A total of 5418 feature films were discovered, which were produced by 78 countries and released from 1921 to 2019. Each film was aired 4.3 times on average. Domestic films (USSR and Russia) and films produced by the USA dominate in the number of broadcasts and views. More often the audience prefers films released in the last decade (2010–2019). The largest audience among the sample groups as a whole was attracted by domestic films shown on holidays on the four Russian channels: “Russia-1”, “Channel One”, “NTV” and “STS”. Differences were found in the size of the male and female TV audiences, which, presumably, can be explained by the psychological mechanisms of self-identification with the characters of films. The age-related typology of adult audience (18+ years old) is revealed, including groups of 18–20 years old, 21–59 years old, and 60+ years old and reflects the specificity of lifestyles due to the behaviour characteristics of the Russian young adults, adults and senior citizens with various social backgrounds.